Etnobotani Zingiberaceae Sebagai Bahan Pengobatan Etnis Karo di Kecamatan Sei Bingai Kabupaten Langkat - Hera Idaman Hati; Jamilah Nasution; Meida Nugrahalia; Abdul Karim (Universitas Medan Area, 2023)
Zingiberaceae is a family of plant species that are efficacious as medicine and are widely used by the Karo ethnic community as ingredients for traditional medicine. The purpose of this study was to determine the species of the Zingiberaceae tribe used as ingredients for traditional medicine by the Karo ethnic community. This research is descriptive qualitative through an emic approach and an ethical approach. The method used is semi-structural interviews conducted openly (open-ended). The results showed eleven species of Zingiberaceae plants used as treatment by the Karo ethnic community, namely Zingiber officinale, Kaemferia galanga, Curcuma domestica, Curcuma xanthorhiza, Alpinia galanga, Zingiber purpureum, Zingiber zerumbet, Amomum compactum, Etlingera elatior, Zingiber ofruminosale, Curcuma vareruginosale. The plant parts used are rhizomes, seeds and flowers. Utilization of Zingiberaceae based on the percentage of interview results obtained 2 groups, namely 80% for treatment, 20% for health.